Emerging Technologies for Librarians: A Practical Approach to Innovation - Yang, Sharon Q; Li, Lili (Chandos information professional series, 2015)
Emerging Technologies for Librarians: A Practical Approach to Innovation focuses on the practical applications of emerging technologies in libraries, defining the technologies in the context of their use in real situations.Each chapter includes an overview of the use of emerging technologies in a particular work area that is followed by a list of.